Web based of mind mapping / Jamiyyah Md Noor - Md Noor, Jamiyyah (Faculty of Information Technology and Quantitative Sciences, 2006)
Nowadays, there are so many sources in education, business and commerce that can get from the changing fast to adopt the computer and Internet technology in what are referred to e-leaning, e-business and e-commerce respectively. The web based is one of the application provides learning convenience complete with audio and graphics. Most of the web based nowadays is more focused on students rather than lecturers to help them increase their ability to study, hi this project, a web based has been developed to provide notes to develop mind map. Using Php can provide more dynamic web based